Properties of oil heat-treated four year-old tropical bamboo gigantochloa levis - Razak Wahab; Mohd Sukhairi Mat Rasat; Mazlan Mohamed; Hashim W. Samsi; Mohd Tamizi Mustafa; Muhammad Iqbal Ahmad (2016)
An investigation on oil heat treatment process conducted on cultivated four year-old Gigantochloa levis bamboo to prolong their service life span. G. levis chosen as this species is easily cultivated and possess good physical, as well as mechanical properties, harvested. Matured culms of four (4) year-old from internodes 5, 6 and 7 in green and air-dried conditions then undergoes heat treated process. Palm oil used as the heating medium in treating the bamboo at temperatures of 140°C, 180°C and 220°C for the durations of 30, 60 and 90 minutes. Air-dried culms exhibited overall higher physical, strength, and durability properties than the green culms. The bamboo heat-treated at 180°C for the duration of 60 min shows an overall quality in both the physical and mechanical studies undertaken. The bamboo also exhibited high durability when tested in the 12 months ground contact tests. Dried bamboos possess better quality in term of properties compared to green bamboo after undergoing heat treatment process. The initial condition of the bamboo, as well as temperatures and duration of the heat treatment process, influence their properties after treatment. An oil-curing process greatly enhanced the durability of the bamboo.